1977
DOI: 10.1016/0304-3959(77)90005-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of root or nerve destruction on vibrotactile sensitivity in trigeminal neuralgia

Abstract: Vibrotactile thresholds were determined at 7 frequencies between 25 and 300 Hz at the medial edge of the cheek in 11 patients who had been or were currently being treated for major trigeminal neuralgia, tic douloureux. A control group, comparable in age but without neural pathology, was also tested. Results indicate essentially no difference between normal and affected sides of the face prior to surgery. The drug carbamazepine (Tegretol), commonly used to control pain of trigeminal neuralgia, did not affect vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
21
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
5
21
0
Order By: Relevance
“…The growth of sensitivity to vibration on the hand. This finding differs from that of Goff et al (1965), who showed that women were generally more sensitive than men, but it is consistent with other reports that vibrotactile sensitivities for the two sexes were approximately equal (Plumb & Meigs, 1961;Steinberg & Graber, 1963;Verrillo & Ecker, 1977). In a recent study (Verrillo, in press), the author measured vibration thresholds in five groups of subjects ranging in mean age from 10 to 65 years.…”
Section: -supporting
confidence: 80%
See 1 more Smart Citation
“…The growth of sensitivity to vibration on the hand. This finding differs from that of Goff et al (1965), who showed that women were generally more sensitive than men, but it is consistent with other reports that vibrotactile sensitivities for the two sexes were approximately equal (Plumb & Meigs, 1961;Steinberg & Graber, 1963;Verrillo & Ecker, 1977). In a recent study (Verrillo, in press), the author measured vibration thresholds in five groups of subjects ranging in mean age from 10 to 65 years.…”
Section: -supporting
confidence: 80%
“…Men, on the other hand, were found to have stable thresholds to 45 years of age before sensitivity decreases. A number of studies, however, found no differences between men and women with respect to vibrotactile threshold measurements (Plumb & Meigs, 1961;Steinberg & Graber, 1963;Verrillo & Ecker, 1977).…”
mentioning
confidence: 99%
“…Not until frequency exceeded 400 Hz did threshold begin to drop abruptly. There is no sign in Barlow's shallow function of Verrillo and Ecker's (1977) Uvshaped branch.…”
mentioning
confidence: 89%
“…This phenomenon, previously studied almost exclusively on the hand, is here shown for the first time to occur on the face as well. Adaptation is then used analytically to determine that the two-branched thresholdversus-frequency function obtained on the face by Verrillo and Ecker (1977) represents the activity of two distinct mechanisms. Action spectra of vibrotactile adaptation reveal the presence of both mechanisms even in subjects whose unadapted threshold function (like that reported by Barlow, 1987) shows no sign of duplexity.…”
mentioning
confidence: 99%
See 1 more Smart Citation